Terry Fox and the National Imaginary: Reading Eric Walters’s Run - MacDonald, Tanis (Studies in Canadian Literature, 2011)
Turning Terry Fox into a fictionalized literary character introduces possibilities for reading “Terry” as a constructed fiction – a “prosthetic” – that claims to be truthful, while also pointing to Fox as a problematic symbol of nationalism, heroism, and sacrifice. Terry Fox is, in the Canadian literary imagination, a perpetual adolescent: consistently called upon to inspire through the tropes of heroism, youth, and determination, and profoundly lost to illness and time. An insistence upon the “true story” mixed with the need to fashion a compelling narrative means that the constructed elements of fiction become even more prominent when set against passionate truth-claims within the text. Eric Walters’s young adult novel Run (2003) is a notable example of Fox’s literary legacy – a legacy shaped by adult writers for consumption by young readers as part of the national imaginary. Run emphasizes the accessibility of mature achievement via Fox’s image as a perpetually adolescent and perpetually heroic persona.